149k views
2 votes
(X-1)(x+6) use the foil method to find the given product

1 Answer

1 vote

With the foil method, we choose to multiply the terms with the rule First Outer Inner Last.

In this case, we have the following expression:


(x-1)(x+6)

then, the following products can be calculated with the FOIL rule:


\begin{gathered} First:x(x)=x² \\ Outer:x(6)=6x \\ Inner:-1(x)=-x \\ Last:-1(6)=-6 \end{gathered}

then, the complete expression is:


x²+6x-x-6=x²+5x-6

therefore, the product is x²+5x-6

User Egermano
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.